Neurocognitive Manifestations of SARSCoV2: A Narrative Review of Mechanisms - Roozbeh, Mahrooz; Roozbeh, Mehrdad; Pakdaman, Hossein; Sobhanian, Seyed Ali; Edalatkhah, Amin; Safari, Saeid (International Clinical Neuroscience Journal, 2020)
Since the outbreak of COVID-19 that is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in 2020 throughout the world, a lot of aspects of people’s lives are affected including their psychological status. Follow-up assessment of survivors of this infection showed that they had multiple psychological disorders including depression, panic attacks, obsessive compulsive disorder, and post-traumatic stress disorder. It is estimated that more than one-third of patients with COVID-19 experience neuropsychiatric symptoms, including headache, paresthesia, and disturbed consciousness. Among patients affected by COVID-19, there are different mechanisms that can cause cognitive dysfunction. COVID-19 can affect the central nervous system (CNS) directly by invasion and indirectly by inducing hypoxia, inflammation, and delirium. The pandemic and fear of infection can also cause anxiety which impairs the cognition as well. By assessing the patients’ cognition and knowing the higher probable cause of cognitive impairment, we can form a better strategy to better treat the impairment. Cognitive behavioral therapy can be effective in reducing the anxiety and cognitive rehabilitation therapy (CRT) can be used to lower the detrimental effects of cognitive impairment caused by COVID-19.